Religious Narratives on Social Media in Shaping the Diversity Attitude of Millennial Generation - Lubis, Putri Handayani; Puspita, Maria; Ahrom Al Ayubbi, Syaefuddin (AT-TURATS, 2025)
This research is motivated by the phenomenon of using social media, especially Twitter, which radical groups use to spread their teachings that clash between religion and diversity. The author tries to analyze the activities of the Twitter account @AlissaWahid, which counters narratives against radical teachings on Twitter with the message of peaceful Islam, Islam rahmatan lil alamin, and Islam that respects differences. As a result, each message posted on Twitter receives a response from followers of the @AlissaWahid account. This research uses a descriptive qualitative approach with a content analysis approach. Data will be collected through observation, in-depth interviews, and documentation. The purpose of this research is to see and explain Alissa Wahid’s behavior or activities in spreading the message of peaceful Islam and respect for diversity. In addition, the author also wants to know whether the content and messages uploaded to his Twitter account are able to shape the attitudes towards diversity of the millennial generation.Penelitian ini dilatarbelakangi oleh fenomena penggunaan media sosial, khususnya Twitter, yang digunakan oleh kelompok radikal untuk menyebarkan ajarannya yang membenturkan agama dan keberagaman. Penulis mencoba menganalisis aktivitas account Twitter @AlissaWahid yang meng-counter narasi-narasi yang melawan ajaran radikal di Twitter dengan pesan Islam yang damai, Islam yang rahmatan lil alamin, dan Islam yang menghargai perbedaan. Hasilnya, setiap pesan yang diposting di Twitter mendapatkan respon dari para pengikut account @AlissaWahid. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pendekatan analisis isi. Data akan dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Tujuan dari penelitian ini adalah untuk melihat dan menjelaskan perilaku atau aktivitas Alissa Wahid dalam menyebarkan pesan Islam yang damai dan menghargai keberagaman. Selain itu, penulis juga ingin mengetahui apakah konten dan pesan yang diunggah ke dalam account Twitternya mampu membentuk sikap keberagaman generasi milenial.